INSPEcT-GUI Reveals the Impact of the Kinetic Rates of RNA Synthesis, Processing, and Degradation, on Premature and Mature RNA Species - de Pretis, Stefano; Furlan, Mattia; Pelizzola, Mattia (Frontiers in Genetics, 2020)
The abundance of RNA species and their response to perturbations are set by the kinetics rates of RNA synthesis, processing and degradation. However, the visualization, interpretation and manipulation of these data require familiarity with mathematical modeling and command line tools. INSPEcT-GUI is an R-Shiny interface that allows researchers without specific training to effortlessly explore how the fine kinetic regulation of the RNA life cycle can shape gene expression programs. In particular, it allows to: (i) interactively visualize gene-level RNA dynamics; (ii) refine the model fit of experimental data; (iii) test alternative regulatory models; (iv) explore, independently from the availability of data, how the combined action of the RNA kinetic rates impacts on premature and mature RNA. INSPEcT-GUI is freely available within the R/Bioconductor package INSPEcT at http://bioconductor.org/packages/INSPEcT/. An HTML vignette including documentation on the tool startup and usage, executable examples, and a video demonstration, are available at: http://bioconductor.org/packages/release/bioc/vignettes/INSPEcT/inst/doc/INSPEcT_GUI.html. ------------------- Only for the review of this manuscript, a fully operational demo version of INSPEcT-GUI is available at https://rnadynamics.shinyapps.io/inspect_gui_standalone/.